Upaya Peningkatan Pengetahuan Penyakit Demam Berdarah Dengue Masyarakat Desa Jelobo Kabupaten Klaten - Latipatul Masruroh; Adji Prayogo; Shinta Listyaningrum; Eny Yusnita; Ayu Ismail; Anggun Dara Tunjung Biru; Luthfi Naaifa Wahyuningtyas; Vinda Prisma Febyola Rahayu; Susanto Susanto; Dwi Handayani; Dwi Astuti; Izzatul Arifah; Nisariati Nisariati (Warta LPM, 2023)
Dengue hemorrhagic fever (DHF) is still a serious problem in Indonesia, because the climate in Indonesia supports mosquito breeding and most Indonesians are still not aware of the importance of clean and healthy living behavior which causes many cities in Indonesia to become endemic cases of DHF. This service is carried out in Jelobo Village, Wonosari District, Klaten Regency, which is included in a DHF endemic area. The morbidity rate reaches 1.71 per 100,000 population and the mortality rate reaches 5% which is included in the 3rd rank of death in the Central Java area. Based on the results of the situation analysis and survey, it shows that the people of Jelobo Village still have less knowledge and attitudes in preventing DHF. The purpose of community service is to increase the knowledge of the Jelobo Village community regarding the understanding, symptoms, causes, and prevention of dengue fever. The method used is by providing online counseling in the form of digital posters and videos distributed through Whatsapp Groups as a preventive and promotive effort to prevent dengue. In addition to using posters and videos that are distributed on Whatsapp Groups, education is also carried out by placing posters in public places. Wilcoxon statistical test obtained p value of 0.00 <0.05, meaning that there is a significant effect on the difference in the treatment given to each variable. A significant difference can also be seen from the results of an increase in the pre-test and post-test of 6.178, so that the treatment given after the pre-test showed an increase in participants' knowledge of DHF disease. Increasing public knowledge will open awareness to create good environmental sanitation so that the chain of disease transmission can be broken. It is necessary to collaborate with health workers, the community, and local village cadres to improve education in the community, especially regarding DHF.